2021
DOI: 10.2196/23905
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Use by Age and Race at a Single Academic Medical Center During the COVID-19 Pandemic: Retrospective Cohort Study

Abstract: Background During the COVID-19 pandemic, many ambulatory clinics transitioned to telehealth, but it remains unknown how this may have exacerbated inequitable access to care. Objective Given the potential barriers faced by different populations, we investigated whether telehealth use is consistent and equitable across age, race, and gender. Methods Our retrospective cohort study of outpatient visits was condu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 10 publications
(12 reference statements)
3
27
1
Order By: Relevance
“…Similar studies in non-neurological populations (10,(22)(23)(24)(25)(26)(27)(28) have shown consistent results with ours, with one study from a large urban health system demonstrating that socially vulnerable populations were more likely to use ED care and office visits in favor of telemedicine care (10). It is interesting to note that multiple studies conducted prior to the COVID-19 pandemic have found that minority status was associated with increased odds of telemedicine utilization in comparison to White patient groups, (29)(30)(31) suggesting that our findings may be in part related to the extraordinary nature of the COVID-19 public health emergency. Nonetheless, taken together with results from previous studies, our findings underscore the presence of important asymmetries in TN access for traditionally disadvantaged patient populations during the COVID pandemic.…”
Section: Discussionsupporting
confidence: 80%
“…Similar studies in non-neurological populations (10,(22)(23)(24)(25)(26)(27)(28) have shown consistent results with ours, with one study from a large urban health system demonstrating that socially vulnerable populations were more likely to use ED care and office visits in favor of telemedicine care (10). It is interesting to note that multiple studies conducted prior to the COVID-19 pandemic have found that minority status was associated with increased odds of telemedicine utilization in comparison to White patient groups, (29)(30)(31) suggesting that our findings may be in part related to the extraordinary nature of the COVID-19 public health emergency. Nonetheless, taken together with results from previous studies, our findings underscore the presence of important asymmetries in TN access for traditionally disadvantaged patient populations during the COVID pandemic.…”
Section: Discussionsupporting
confidence: 80%
“…A recent study by Stevens et al of a general patient sample showed that older patients were more likely to use telehealth in visits during the early COVID-19 pandemic, though in that study, they were less likely to use video technology than younger patients. 45 Caregivers are frequently present for cancer patients and may be an important support for helping older patients to use telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has inevitable impact for medical care of other systemic diseases, especially the cardiovascular disease [ 3 ]. During the COVID-19 pandemic, many hospitals gave priority to treating COVID-19 patients and even reduced in-person ambulatory care [ 4 ]. Moreover, screening for COVID-19 will delay the time of management.…”
Section: Introductionmentioning
confidence: 99%